2017
DOI: 10.1074/jbc.m117.805036
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial arginine glycosyltransferase effector NleB preferentially modifies Fas-associated death domain protein (FADD)

Abstract: The inhibition of host innate immunity pathways is essential for the persistence of attaching and effacing pathogens such as enteropathogenic (EPEC) and during mammalian infections. To subvert these pathways and suppress the antimicrobial response, attaching and effacing pathogens use type III secretion systems to introduce effectors targeting key signaling pathways in host cells. One such effector is the arginine glycosyltransferase NleB1 (NleB in ) that modifies conserved arginine residues in death domain-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…This observation, in conjunction with increased levels of Arg-GlcNAcylation seen during overexpression, suggested that many substrates may be non-authentically glycosylated when the effectors are overexpressed. These findings are similar to a previous report that suggested overexpression of NleB1 also results in Arg-GlcNAcylation of a broader range of substrates [13]. We note in particular the numerous two-component response regulators that were Arg-GlcNAcylated during overexpression of SseK1 (Fig 2A, Supplementary Table 1), perhaps suggesting a mechanism for effector-mediated regulation of two-component signaling outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This observation, in conjunction with increased levels of Arg-GlcNAcylation seen during overexpression, suggested that many substrates may be non-authentically glycosylated when the effectors are overexpressed. These findings are similar to a previous report that suggested overexpression of NleB1 also results in Arg-GlcNAcylation of a broader range of substrates [13]. We note in particular the numerous two-component response regulators that were Arg-GlcNAcylated during overexpression of SseK1 (Fig 2A, Supplementary Table 1), perhaps suggesting a mechanism for effector-mediated regulation of two-component signaling outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…While these studies have demonstrated the ability of SseK1 to GlcNAcylate a given target, the approach is substrate specific and there requires knowledge of the potential targets. To identify the full range of host Arg-GlcNAcylated substrates, we developed a quantitative approach using mass spectrometry (MS) to enrich for arginine glycosylated peptides [13]. Using peptides derived from host cells infected with S. Typhimurium ΔsseK123 over-expressing either SseK1 or inactive SseK1 E255A , label-free MS based quantification revealed a broad range of substrates that were only modified in the presence of active SseK1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations